2006
DOI: 10.1111/j.1423-0410.2006.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion audit of fresh‐frozen plasma in southern Taiwan

Abstract: Hospital policy, computerized transfusion guidelines and periodic audits greatly reduced inappropriate FFP transfusions. An educational campaign had a more limited effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…This is important to prevent misuse which may lead to shortage of blood availability and thus denial of blood supply to someone in a life-threatening situation. The importance of an internal audit and education programs, emphasizing proper selection of blood components for patients and avoiding their overuse, has been highlighted by various authors who reported a marked decline in inappropriate demands for blood products after such audits were followed by educational sessions for clinicians [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important to prevent misuse which may lead to shortage of blood availability and thus denial of blood supply to someone in a life-threatening situation. The importance of an internal audit and education programs, emphasizing proper selection of blood components for patients and avoiding their overuse, has been highlighted by various authors who reported a marked decline in inappropriate demands for blood products after such audits were followed by educational sessions for clinicians [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…It should in fact, be the aim of all blood banks to achieve even higher rates of appropriate transfusion of various blood products. Yeh et al carried out audit on FFP usage and followed it by fi ve sessions of education on transfusion guidelines which resulted in 30% decrease in inappropriate FFP usage [2]. Hawkins TE instituted a system of pre-transfusion approval which resulted in 33% decrease in units of FFP transfused [3].…”
Section: Discussionmentioning
confidence: 99%
“…After full texts were examined, 24 records were judged to be eligible. Fourteen records excluded after examining full texts are shown in Supplementary Table S2 [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Search Resultsmentioning
confidence: 99%
“…In four studies an educational program was undertaken to circulate evidence‐based guidelines, to illustrate adverse effects of transfusions, to avoid unnecessary risks, to improve the efficient data supplies necessary for rational transfusion of FFP, and to critically review and discuss transfusion episodes. 1,11,22,23 …”
Section: Resultsmentioning
confidence: 99%